Pengaruh Kepuasan Kerja, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi di Biro Keuangan dan Barang Milik Negara Kementerian Pertanian Pada Masa Pandemi Covid-19) - Fandi (2021)
Research the quantitative research was conducted to determine the influence of job satisfaction, motivation and work discipline on the performance of employees of the Bureau of Finance and the State Property of the Ministry of Agriculture. The population conducted in this study are employees of the Bureau of Finance and the State Property of the Ministry of Agriculture in the year 2021. The sample is done by using non-probability sampling method, and the technique used is purposive sampling. Sources of information in this research is obtained by spreading the questionnaire on the 78 respondents were employees of the Bureau of Finance and the State Property of the Ministry of Agriculture. Hypothesis testing and the analysis used is descriptive analysis and inferential, the application of information processing data wear PLS 3.3 with a level of significance of 5%. The results of this research are ( 1) job satisfaction has a significant influence on employee performance.( 2) motivation has a significant influence on employee performance.( 3) the discipline of work has influence signifikanterhadap employee performance.